Effect of Terrain Size Over the Performance of Proactive & Reactive Protocol in MANET with Varying Nodes (International Journal of Communication Systems and Network Technologies, 2024)
Mobile ad hoc network is a hot area of research in wireless communication. Ad hoc network is the collection of no. of nodes. Nodes are free to move from one place to another place. Due to movement of nodes in ad-hoc network, topology is always random & they form a temporary network. A detailed study & simulation result of proactive and reactive routing protocol with different terrain size, data rate & variable nodes (small & large wireless network) are represented in this research paper. Simulation is carried out by using NS2 simulator. Performance of protocol totally based on some performance metrics like PDF (packet Delivery Fraction), Packet loss & End to End Delay.
Keywords: MANET; AODV; DSDV; PDF; End to End Delay; Packet Loss; NS-2